Prioritas Daerah Rawan Banjir di Kota Singkawang dengan Metode AHP Berbasis WEBGIS - Arif Imaduddin; Syarifah Putri; Istikoma Istikoma (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Flooding is one of the natural disasters that frequently occurs in Singkawang City and has a significant impact on infrastructure, economic activities, and the social life of the community. High rainfall, relatively flat topography, suboptimal drainage systems, and changes in land coverare the main factors causing an increased risk of flooding in this region.